An early developmental vertebrate model for nanomaterial safety: bridging cell-based and mammalian toxicity assessment. (March 2016) - Webster, Carl A; Di Silvio, Desire; Devarajan, Aarthi; Bigini, Paolo; Micotti, Edoardo; Giudice, Chiara; Salmona, Mario; Wheeler, Grant N; Sherwood, Victoria; Bombelli, Francesca Baldelli
Aim: With the rise in production of nanoparticles (NPs) for an ever-increasing number of applications, there is an urgent need to efficiently assess their potential toxicity. We propose a NP hazard assessment protocol that combines mammalian cytotoxicity data with embryonic vertebrate abnormality scoring to determine an overall toxicity index.Results: We observed that, after exposure to a range of NPs, Xenopus phenotypic scoring showed a strong correlation with cell based in vitro assays. Magnetite-cored NPs, negative for toxicity in vitro and Xenopus, were further confirmed as nontoxic in mice.Conclusion: The results highlight the potential of Xenopus embryo analysis as a fast screening approach for toxicity assessment of NPs, which could be introduced for the routine testing of nanomaterials.